A laser-micromachined polymeric membraneless fuel cell - Li, Aidan (2012)
This paper presents a laser-micromachined polymeric membraneless fuel cell. The membraneless fuel cell, constructed with three polymethyl methacrylate (PMMA) layers, takes advantage of two laminar flows in a single micro channel to keep the fuel and oxidant streams separated yet in diffusional contact. Laser micromachining was employed to make the flow channel and electrode substrate based on PMMA. The anode and cathode electrodes were fabricated by wet-spraying catalyst inks onto the gold-coated PMMA substrate. The packed fuel cell has been electrochemically characterized by an electrochemical analyser. The membraneless fuel cell works stably with Reynolds numbers ranging from 7.65 to 30.6. At room temperature, the laminar-flow-based micro membraneless fuel cell can reach a maximum power density of 0.58 mW/cm2 with 0.5 M HCOOH in 0.1 M H2SO4 solution as fuel and O2 saturated 0.1 M H2SO4 solution as oxidant. When 0.01 M H2O2 in 0.1 M H2SO4 solution is used as oxidant, a maximum power density of 1.98 mW/cm2 is obtained. The paper reports for the first time the use of hydrogen peroxide in sulfuric acid as the oxidant. The new oxidant composition allows a simple recycling process and better fuel utilization.